Laser interaction with undercritical foams of different spatial structures - J. Limpouch; V. Tikhonchuk; O. Renner; Sh. Agarwal; T. Burian; J. Červenka; J. Dostál; R. Dudžák; D. Ettel; A. Gintrand; L. Hudec; L. Juha; et al. (Matter and Radiation at Extremes)
The interaction of high-power laser pulses with undercritical foams produced by different techniques but with the same average density is studied at the PALS laser facility. The spatial–temporal evolution of X-ray emission is observed using an X-ray streak camera, electron and ion temperatures are measured by X-ray spectroscopy, and hot-electron production is characterized by monochromatic X-ray imaging. Transmission of a femtosecond laser probe pulse through foams is observed in the near and far fields. In spite of large differences in pore size and foam structure, the velocity of ionization front propagation is quite similar for all the foams studied and is slower than that in a homogeneous material of the same average density. The ion temperature in the plasma behind the ionization front is a few times higher than the electron temperature. Hot-electron production in plastic foams with small pores is strongly suppressed compared with that in solid targets, whereas in foams produced by additive manufacturing, it is significantly increased to the level observed in bare copper foil targets.